AIE-active organic polymorphs displaying molecular conformation-dependent amplified spontaneous emissions (ASE). (February 2018) - Liu, Huapeng; Lu, Zhuoqun; Tang, Baolei; Zhang, Zuolun; Wang, Yue; Zhang, Hongyu
Abstract: The Schiff base ( E )-4-chloro-2-(((4-(dimethylamino)phenyl)imino)methyl)phenol showing aggregation-induced emission has been found to form brightly yellow- and orange-emissive organic polymorphs. As indicated by the photophysical studies, the suppression of nonradiative excited-state decay and the improvement of radiative decay are responsible for the emission enhancement from solutions to crystalline polymorphs. Crystallographic studies disclose that the two polymorphs adopt quite similar molecular packing modes but different molecular conformations. Thus, the difference in emission colors of the two polymorphs is mainly attributed to the influence of molecular conformations. For the rod-like orange-emissive polymorph, ultralong single crystals can be prepared, and these crystals show the attractive property of low-loss optical waveguide. More importantly, both polymorphs exhibit amplified spontaneous emission properties. This study provides a good model system for understanding the influence of molecular conformations on solid-state luminescent properties by minimizing the intervention of molecular packing modes in luminescent performance. Moreover, the study further confirms that the utilization of organic polymorphs can be a facile strategy to realize multicolor crystal lasing. Graphical abstract: Highlights: Two types of AIE-active organic crystals exhibiting polymorph-dependent emission have been prepared. Organic polymorphs possessing similar packing modes but different molecular conformations have been achieved. Yellow and orange amplified spontaneous emissions have been achieved based on organic polymorphs.